hi,
anyone got some ideas on figuring out this answer to the attached question.
Thanks
.
I presume that the "question" is in the second, uncompleted, "equation".
If $\displaystyle x= \sqrt{k}+ \frac{1}{\sqrt{k}}+ 1$ then $\displaystyle x^2- 2x= $. Looks to me like its just a matter of doing the calculation.
$\displaystyle x^2= (\sqrt{k}+ \frac{1}{\sqrt{k}}+ 1)^2= (\sqrt{k}+ \frac{1}{\sqrt{k}})^2+ 2(\sqrt{k}+ \frac{1}{\sqrt{k}})+ 1$
$\displaystyle -2x= 2(\sqrt{k}+ \frac{1}{\sqrt{k}})+ 2$ so subtracting just gives
$\displaystyle (\sqrt{k}+ \frac{1}{\sqrt{k}})^2- 1$
Go ahead and multiply that square and see what you get.